Walsh, Daphne. New Perlican Photograph of a man holding a small child. - Barrett, Terra (1950)
A photograph of William Hobbs holding a small child - unknown girl (possibly Hazel, older sister) circa 1950 in front of a house with a picket fence. Above the photo says "Family Memories" and below the photo says "Dad." The photograph was printed by Kodak.